The evaluation of the effect of estrogen administration on cutaneous wound healing in Staphylococcus aureus-infected diabetic and nondiabetic mice - Kanae Mukai; Kohei Ogura; Yukari Nakajima; Toshio Nakatani (PLoS ONE, 2025)
Diabetes-related infection has become a difficult and significant global public health issue. Estrogen has specific hormones that promote cutaneous wounds in diabetic mice . However, the impact of estrogen on skin-colonized pathogenic bacteria is unknown. The purpose of this study was to look into how estrogen affects wounds infected with Staphylococcus aureus . Nondiabetic db/ + mice and diabetic db/db mice were both injured, and bacterial suspension was applied to each wound site. Estrogen or vehicles were injected intraperitoneally every 3–4 days after wounding. S. aureus infection impaired diabetic wounds and reduced collagen deposition. Immunostaining revealed that S. aureus infection reduced the number of blood and lymphatic vessels while increasing the number of neutrophils in nondiabetic wounds, regardless of estrogen treatment. Conversely, estrogen administration reduced the number of macrophages in S. aureus- infected nondiabetic wounds compared to vehicle-treated wounds. The number of lymphatic vessels was roughly double that of estrogen administration in S. aureus -infected nondiabetic wounds. Our findings showed that S. aureus infection in diabetic wounds delayed cutaneous wound healing due to excessive inflammation, inhibited collagen deposition, and impaired angiogenesis or lymphangiogenesis, although estrogen administration did not reverse these effects. Our findings also revealed that estrogen administration effectively treated S. aureus -infected nondiabetic wounds by regulating the immune response and increasing the synthesis of lymphatic vessels .